Directive 2014/24/EU and the implementation of e-Procurement in Portugal – Part II - Carvalho, Raquel (2020)
This Part II concludes the paper published in EPPPL 1-2019 regarding the implementation of e-procurement in Portugal. In Part I, the evolution regarding e-procurement provisions within Public Procurement Directives from 2004 to 2014 was addressed. Part II now addresses how both the Public Contracts Code and the specific legislation regarding electronic platforms have transposed the 2014 Public Procurement Directives into internal law, namely: (i) how the transposition of articles 29, 22, 40 and annexes of the 2014 Directives was made [not only the legal regime but also how some litigious questions were taken (and solved) to national administrative courts]; (ii) how the first intention of the Legislator to transpose the 2014 Directives went; and (iii) how they were actually effectively transposed. As already referred to in Part I, the transposition of the 2014 Directives in Portugal was made through a two-step procedure. Article 22 of the 2014/24/Directive was regulated by Law 96/2015, a very extensive and complex regulation regarding e-procurement, while the remaining provisions of the 2014 Directives were transposed in 2017 after a period of public discussion of a very different draft. The path that has been built since 2004 is, thus, consolidated.